Modelling and Evaluation of the Effect of Temperature on the Rheological Properties of Drilling Mud Formulated with Local Barite - Ngoz, Nnadi Chidiebere; Koyejo, Oduola Mujeeb; Friday, Joel Ogbonna (SSRG International Journal of Chemical Engineering Research, 2021)
This research paper assesses the effect of temperature on the rheological properties of Water-Based and Oil-Based Muds. The Muds were formulated with locally sources barite from 5 locations in Nigeria.Third order polynomial models have been considered to model the rheological properties as a function of SG (Specific gravity) which were generated using least square method and regressed with the Excel GRG (Generalized Reduced Gradient) Non-Linear Forward derivative solver. The absolute mean percentage error of the model data and measured data were calculated for all rheological properties and WBM 10” Gel strength had the highest error of 6.578% followed by OBM Yield Point of 4.443%. WBM Plastic viscosity showed the least error of 0.315%, seconded by WBM 10’ Gel strength with error of 0.339%. Findings from this work indicated that barites Samples B3 and B5 are good barites for WBM formulation as their rheology withstood increasing temperature the most and B4 is better for OBM formulation. Also, B1 and B2 will be good for OBM formulation if beneficiated to increase its SG and remove impurities.
Keywords: Barite; Modelling; Oil-based mud; Rheology; Water based-mud; Université de Ouaga; CFOREM